The Hills Have Eyes: An Approach Towards Eco-Marxism Policies and Land Ethics - Youliang Chen (Journal of Dharma, 2025)
The world continues to grapple with economic challenges as ancient as human civilization itself. Recent scholarship increasingly explores ecological crises through socio-economic perspectives, particularly within Marxist frameworks. Yet, one crucial dimension often remains overlooked—the notion of predestination that subtly shapes human interpretations of environmental devastation. From certain Christian viewpoints, ecological destruction is sometimes misunderstood as a divinely predetermined consequence of the original sin of Adam and Eve. Such a misreading, grounded in fatalism, risks portraying ecological degradation as inevitable rather than as the moral and material outcome of human action. This study extends the discourse by integrating the concept of predestination into eco-Marxist critiques of self-interest—the very force driving humanity’s destructive pursuit of profit at the expense of ecological balance. In this context, the idiom “The Hills Have Eyes” is reinterpreted as an ecological metaphor, suggesting that nature itself bears witness to human excesses and responds through environmental retribution. Hence the author argues for a synthesis of eco-Marxist theory with land ethics and sustainable policy frameworks, urging a shift from human-centered exploitation toward ecological responsibility and collective stewardship.